Annual Trends in the Incidence and Prevalence of Alzheimer's Disease in South Korea: A Nationwide Cohort Study - Baek, Min Seok; Kim, Han-Kyeol; Han, Kyungdo; Kwon, Hyuk-Sung; Na, Han Kyu; Lyoo, Chul Hyoung; Cho, Hanna (Frontiers in Neurology, 2022)
Despite recent studies suggesting a declining incidence and prevalence of dementia on a global scale, epidemiologic results with respect to Alzheimer's disease (AD) are lacking due to the methodological limitations inherent to conducting large-scale cohort investigations of this topic. The aim of the current study was to investigate the incidence and prevalence of AD in Korea. We conducted a secondary analysis within the National Health Insurance System (NHIS) database, a unique resource that reports medical information for the entire Korean population. AD diagnoses as well as evaluations of vascular risks were defined based on International Statistical Classification of Diseases (ICD-10) codes along with prescription records. The cut-off age for diagnosing AD was defined as the age of the patient's highest Youden index. In this study, the incidence and prevalence of AD in the Korean population aged 40 years or older showed an overall increase between 2006 and 2015. Although both older and younger age groups showed an increase in the incidence and prevalence of AD, the highest increase was observed in older age groups. Based on the highest Youden's index value (sensitivity + specificity – 1), the cut-off value for the diagnosis of AD was 69 years with an area under the curve (AUC) of 0.92. We found that the incidence of AD was higher in individuals with underlying vascular risks. However, in recent years, the prevalence of AD was conversely found to be lower in individuals with hypertension or dyslipidemia. Despite efforts toward reducing the number of AD cases through educational, policy, and various public health and preventive medicine interventions, the incidence and prevalence of AD continues to grow in Korea. Efforts aimed at early diagnosis and the modification of underlying risks may be critical to reducing the socioeconomic burden of AD.